Results of Long-Term Treatment and Rehabilitation of Drug Addicts "Mini Thanyarak" Case study of Akat Amnuay Hospital, year 2023 - Suttawanit, Jirattikal; Mungkhampha, Patcharin; Phanawong, Nava (Journal of The Department of Medical Services, 2024)
Background:. According to policies and strategies towards drugs, the perspective towards addicts has changed from viewing them as addicts to patients who require treatment. Patients’ access to rehabilitation and treatment leads to a shortage of hospital beds. Therefore, a concept of developing a long-term treatment and rehabilitation model has been introduced under the name “Mini Thanyarak”, which can be applied to community hospitals. Objective: To study the results of long-term treatment and rehabilitation of drug addicts “Mini Thanyarak” model, which was a case study at Akat Amnuay Hospital. Method: This research was evaluation research. The sample group was a group of 13 people who received treatment and rehabilitation between August and November 2023.. The tools used were guidelines for the implementation of long-term rehabilitation of drug and narcotic users in community hospitals, using the Mini Thanyarak model, and a manual for cognitive and behavioral therapy in drug and substance addicts in the rehabilitation period by Saengdueanchai S, et al. Data were collected from individual records, activity records and observations. Data analysis was done by using qualitative data with classification to inductively analyze and interpret meanings, draw conclusions, and explain the phenomena. Quantitative data were collected by using frequency, percentage and average analysis. Results: The recipients remained in the treatment and rehabilitation system for 90 days without any complications. When using psychosocial therapy, there were positive behavioral changes and self-defense skills. Follow-up results 3 months after treatment were excellent; it was found that 84.6% did not return to drug use again. Conclusion: The Mini Thanyarak model results in no relapse into addiction and behavioral changes. Thus, the model could be used to stop drug addiction.